Cardiac changes during the peri‐menopausal period in a VCD‐induced murine model of ovarian failure. (31st May 2019) - Fernandes, Rosephine Del; Hall, Alexandra; Ferguson, Melissa; Lorenzen‐Schmidt, Ilka; Balasubramaniam, Vishali; Pyle, W. Glen
Abstract: Aim: Cardiovascular disease (CVD) risk is lower in pre‐menopausal females vs age matched males. After menopause risk equals or exceeds that of males. CVD protection of pre‐menopausal females is ascribed to high circulating oestrogen levels. Despite experimental evidence that oestrogen are cardioprotective, oestrogen replacement therapy trials have not shown clear benefits. One hypothesis to explain the discrepancy proposed hearts remodel during peri‐menopause. Peri‐menopasual myocardial changes have never been investigated, nor has the ability of oestrogen to regulate heart function during peri‐menopause. Methods: We injected female mice with 4‐vinylcyclohexene diepoxide (VCD, 160 mg/kg/d IP) to cause gradual ovarian failure over 120d and act as a peri‐menopausal model Results: Left ventricular function assessed by Langendorff perfusion found no changes in VCD‐injected mice at 60 or 120 days compared to intact mice. Cardiac myofilament activity was altered at 60 and 120 days indicating a molecular remodelling in peri‐menopause. Myocardial TGF‐β1 increased at 60 days post‐VCD treatment along with reduced Akt phosphorylation. Acute activation of oestrogen receptor‐α (ERα) or ‐β (ERβ) depressed left ventricular contractility in hearts from intact mice. ER‐regulation of myocardial and myofilament function, and myofilament phosphorylation, were disrupted in the peri‐menopausal model. Disruption occurred without alterations in total ERα or ERβ expression. Conclusions: This is the first study to demonstrate remodelling of the heart in a model of peri‐menopause, along with a disruption in ER‐dependent regulation of the heart. These data indicate that oestrogen replacement therapy initiated after menopause affects a heart that is profoundly different from that found in reproductively intact animals.